A preliminary survey of urinary tract infection in females attending at private clinics in Baglung Municipality, Nepal - Pokhrel, Yam Bahadur (Dhaulagiri Journal of Contemporary Issues, 2026)
Urinary tract infection is the effect of microbial pathogen such as bacteria and other microorganism that destroy the mucous layer of urinary tract and genital tract in both male and female individual of the community. This study investigated the prevalence rate of urinary tract infection among females visiting private clinic in Baglung Municipality. This research was conducted from Baisakh to Ashar 2080 at Jharana and Sapana clinic in hospital road, Baglung bazar by survey and experimental methods. Total 141 urine samples were purposively collected and tested by macroscopic, microscopic, wet film and gram staining methods. Data were also collected by interviews, questionnaire observation methods to find out knowledge, attitude and practice concerning UTI. This finding exposed a high prevalence of UTI diseases among child bearing females (61.39%) as compared to child not bearing female (35%) with a statistically significant difference (X2cal = 8.03, X2cal>X20.05 at 1 d.f.). UTI infection was also higher among females participating in cooperative and agricultural occupational field without statistically significant difference p=0.066>0.05 (X2cal =11.84, X2cal>X20.05 at 6 d.f.). This study highlight the requirement of health awareness program, hygienic toilet, improved sanitation, personal hygiene, balanced diet and proper treatment to reduce infection of UTI disease in the community.